Human Rights Protection in Antitrust Law: Integrating the Principle of Dignified Justice into Antitrust Policy in Europe and Asia - Akyuwen, Rory Jeff; Labetubun, Muchtar Anshary Hamid; Chansrakaeo , Ruetaitip (Jurnal Suara Hukum, 2025)
Human rights must be integrated into Antitrust law to ensure social justice and protection for vulnerable groups, considering that the dominant economic approach often overlooks the negative impacts of monopolistic and anti-competitive practiceson the fundamental rights of individuals and communities. The aim of this research is to analyze how the integration of the principle of dignified justice in Antitrust law can strengthen human rights protection in Europe and Asia, as well as to evaluate the extent to which Antitrust law in both regions has currently accommodated human rights protection. This research uses a normative legal method with legislative, conceptual, and comparative approaches to analyze the integration of the principle of dignified justice in Antitrust law in Europe and Asia, and to assess human rights protection through qualitative analysis of relevant regulations, doctrines, and court rulings. The research findings show that the integration of the principle of dignified justice in Antitrust law in Europe and Asia strengthens human rights protection by creating a balance between entrepreneurial freedom and protection for vulnerable groups. Europe, through regulations such as the TFEU and initiatives like the Digital Markets Act, has made more progress in accommodating human rights, while Asia, though beginning to adopt the principle of justice in countries like Japan and Indonesia, still faces challenges in harmonizing regulations and enforcing the law. Collaboration and the adoption of best practices are expected to further strengthen human rights protection in Antitrust law in both regions. The research recommends that countries in Europe and Asia need to explicitly integrate human rights principles, particularly dignified justice, into the formulation and implementation ofcompetition law to ensure the protection of vulnerable groups.